Microgrids for Extraterrestrial Habitats: A Review of Technologies, Needs, and Challenges - Leila Chebbo; Muhammed Ali Gultekin; Ali Bazzi; Sean A. Q. Young; Joseph P. Kozak (IEEE Access)
The National Aeronautics and Space Administration (NASA) and other space organizations are preparing for new space exploration and habitation initiatives. These include human return to the Moon through the Artemis mission, human exploration of Mars and deeper space habitats, and the establishment of permanent human bases on the Moon, Mars, and beyond. Such installations demand a highly reliable, resilient, safe, and autonomous power system to support the habitats’ different functions, systems, and electrical loads. This paper presents a review of the different power sources, energy storage options, microgrid architectures, in addition to challenges and needs for future extraterrestrial habitat microgrids. In addition, this paper reviews the economic challenges and life cycle costs of future extraterrestrial microgrids. Of special focus in this paper are the degradation causes and mechanisms of space microgrid components due to harsh environments in which such microgrids will operate. With the information presented in this paper, which accurately compares different technologies’ performance for the same function, researchers in the space community will be able to make better decisions regarding the requirements and technology development of an extraterrestrial power system.